Sacral slope change from sanding to relaxed-seated grossly overpredicts the presence of a stiff spine - Sharma, Abhinav Kumar; Grammatopoulos, George; Pierrepont, Jim W.; Madurawe, Chameka S.; Innmann, Moritz Maximilian; Vigdorchik, Jonathan M.; Shimmin, Andrew J. (The journal of arthroplasty, 2023)
Background - Several authors propose that a change in sacral slope of ≤10° between the standing and relaxed-seated positions (ΔSSstanding→relaxed-seated) identifies a patient with a stiff lumbar spine and has suggested the use of dual-mobility bearings for such patients undergoing a total hip arthroplasty (THA). The aim of this study was to assess how accurately ΔSSstanding→relaxed-seated can identify patients with a stiff spine. - Methods - A prospective, multicentre, consecutive cohort series of 312 patients had standing, relaxed-seated, and flexed-seated lateral radiographs prior to THA. ΔSSstanding→relaxed-seated was determined by the change in sacral slope between the standing and relaxed-seated positions. Lumbar flexion (LF) was defined as the difference in lumbar lordotic angle between standing and flexed-seated. LF ≤20° was considered a stiff spine. The predictive value of ΔSSstanding→relaxed-seated for characterizing a stiff spine was assessed. - Results - A weak correlation between ΔSSstanding→relaxed-seated and LF was identified (r2 = 0.13). Eighty six patients (28%) had ΔSSstanding→relaxed-seated ≤10° and 19 patients (6%) had a stiff spine. Of the 86 patients with ΔSSstanding→relaxed-seated ≤10°, 13 had a stiff spine. The positive predictive value of ΔSSstanding→relaxed-seated ≤10° for identifying a stiff spine was 15%. - Conclusion - In this cohort, ΔSSstanding→relaxed-seated ≤10° was not correlated with a stiff spine. Using this simplified approach could lead to a 7-fold overprediction of patients with a stiff lumbar spine and abnormal spinopelvic mobility, unnecessary use of dual-mobility bearings, and incorrect component alignment targets. Referring to patients with ΔSSstanding→relaxed-seated ≤10° as being stiff is misleading. The flexed-seated position should be used to effectively assess a patient’s spine mobility prior to THA.
Gesehen am 09.06.2023